Molecular Identification of Elvers (Anguilla spp.) from River Estuaries in Central Java, Indonesia Using DNA Barcoding Based on mtDNA CO1 Sequences - Iffan Nadhif Falah; Ratih Ida Adharini; Susana Endah Ratnawati (Jurnal Ilmiah Perikanan dan Kelautan, 2023)
Highlight Research The elvers of Anguilla were identified through the morphological and molecular markers The result of morphological and molecular identification is different The molecular identification helps to confirm the morphological identification Based on this study molecular identification of the elvers of Anguilla found in river estuaries of Central Java is Anguilla bicolor bicolor   Abstract An inventory of the presence and diversity of Anguilla spp. needs to be carried out as a basis for sustainable resource management. Conventional techniques based on morphological characteristics”are often less effective considering the morphological characteristics of Anguilla spp. are very identical and not so many can be observed, especially at the young eel stage. DNA-based molecular identification can be a way to determine diversity and phylogeny for conservation and inventory purposes. This research aimed to determine the diversity and phylogeny of Anguilla spp. obtained at the estuaries of Serayu River in Cilacap, Luk Ulo River in Kebumen, and Jali River in Purworejo in Central Java, Indonesia. A total of 10 samples were taken from each research location were analyzed morphologically, then it is known that there are 4 morphologically different samples at each research location so that a total of 12 samples were taken for molecular analysis. MEGA was used to construct the phylogenetic trees via Neighbour Joining (NJ) algorithms using the Kimura 2-parameter model with uniform rates and obtained by 1000 bootstraps replication. There are four species of Anguilla spp. identified morphologically, namely Anguilla bicolor bicolor, Anguilla bicolor pacifica, Anguilla obscura, and Anguilla australis. The species of Anguilla spp. that is molecularly identified is Anguilla bicolor bicolor with an identity percentage of > 98%. All samples are also known to be related to Anguilla bicolor bicolor identified in other countries.